2023
DOI: 10.1021/acs.joc.2c02460
|View full text |Cite
|
Sign up to set email alerts
|

Extending Photocatalyst Activity through Choice of Electron Donor

Abstract: Sacrificial additives are commonly employed in photoredox catalysis as a convenient source of electrons, but what occurs after electron transfer is often overlooked. Tertiary alkylamines initially form radical cations following electron transfer, which readily deprotonate to form strongly reducing, neutral α-amino radicals. Similarly, the oxalate radical anion (C2O4 •–) rapidly decomposes to form CO2 •– (E 0 ≈ −2.2 V vs SCE). We show that not only are these reactive intermediates formed under photoredox condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Given the redox potential of 4CzIPN ( E (PC*/PC •– ) = 1.35 V vs SCE; E (PC/PC •– ) = −1.21 V vs SCE), these observations explain the experimental outcome: the use of a conventional acid such as HBF 4 resulted in a low yield of 3a due to a thermodynamically unfavorable SET between 4CzIPN and the corresponding phosphonium salt P + BF 4 – (Table , entry 2). On the other hand, the use of (CO 2 H) 2 ·2H 2 O was effective because the resulting phosphonium oxalate P + OA – could be oxidized by 4CzIPN to generate the potent reductant CO 2 •– via the decomposition of the oxalate radical anion (Table , entry 6) . Thus, we next sought to obtain evidence for the generation of CO 2 •– by capturing it with 1,1-diphenylethylene ( 4 ) as a radical-trapping agent (Figure , 2C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the redox potential of 4CzIPN ( E (PC*/PC •– ) = 1.35 V vs SCE; E (PC/PC •– ) = −1.21 V vs SCE), these observations explain the experimental outcome: the use of a conventional acid such as HBF 4 resulted in a low yield of 3a due to a thermodynamically unfavorable SET between 4CzIPN and the corresponding phosphonium salt P + BF 4 – (Table , entry 2). On the other hand, the use of (CO 2 H) 2 ·2H 2 O was effective because the resulting phosphonium oxalate P + OA – could be oxidized by 4CzIPN to generate the potent reductant CO 2 •– via the decomposition of the oxalate radical anion (Table , entry 6) . Thus, we next sought to obtain evidence for the generation of CO 2 •– by capturing it with 1,1-diphenylethylene ( 4 ) as a radical-trapping agent (Figure , 2C).…”
Section: Resultsmentioning
confidence: 99%
“…•− via the decomposition of the oxalate radical anion (Table 2, entry 6). 24 Thus, we next sought to obtain evidence for the generation of CO 2…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, the use of (CO2H)2•2H2O was effective because the resulting phosphonium oxalate P + OAcan be oxidized by 4CzIPN, probably followed by the degradation of the oxalate anion to generate potent reductant CO2 •− (Table 2, entry 6). 21 Thus, we next sought to obtain the evidence for generation of CO2 •− by capturing it with 1,1-diphenylethylene (4) as a radical-trapping agent (Figure 3, 2-C). Indeed, after a reaction of P2' with 4 under optimal conditions, the expected radical adduct 6 could be detected by 1 H NMR analysis and high-resolution mass spectrometry (HRMS) along with 5 as the major product.…”
Section: Resultsmentioning
confidence: 99%
“…Based on all the spectroscopic evidence and analysis of structural data, it was demonstrated that the reaction from A to B proceeded smoothly with a loss of aromaticity and partially semi‐saturation of the dtb‐dpy ligand following the initial photoinitiated electron transfer between A and TEA. Furthermore, the scope of ancillary ligands which determined photochemical stability was screened to show effects and reactivity in chemical synthesis [15e,23] …”
Section: Discussionmentioning
confidence: 99%